Effect of Walking Exercise on Blood Parameters in Patients with Type 2 Diabetes Mellitus - Raziye Şavkın; Nihal Büker; Gökhan Bayrak; Gülsüm Oğuz; Şenay Topsakal (İstanbul Medical Journal, 2021)

(untitled)
Introduction:Lifestyle modification is the first-line treatment for the management of patients with type 2 diabetes mellitus (T2DM). Patient education and the use of technological tools that will increase compliance with the exercise program may increase physical activity in these patients. In this study, we aimed to examine the effect of pedometer-based walking intervention on clinical, diabetes-related cognitive and social factors, and quality of life outcomes in patients with T2DM.Methods:Forty patients (17 male and 23 female) were randomly divided into the intervention (n=20; 13 male and 7 female) and control (n=20; 4 male and 16 female) groups. Both groups received diabetes education program, and instant messaging and calling application were used to facilitate and increase the communication between patients and researchers. The intervention group underwent the brisk walking program (40 minute/day and 3 times/week) for 12 weeks. The outcomes included the plasma glucose, hemoglobin A1c (HbA1c), blood lipids, body mass index, International Physical Activity Questionnaire-Short Form (IPAQ-SF), Multidimensional Diabetes Questionnaire, SF-36, and daily number of steps.Results:The HbA1c level decreased significantly in the intervention group (p=0.020). No statistically significant difference was observed within and between groups in terms of the plasma glucose and lipid levels (p≥0.05). The IPAQ-SF walking and total physical activity scores increased in the intervention group (p<0.001) and had better results in diabetes-related cognitive and social factors and the quality of life (p<0.001).Conclusion:Diabetes education, mobile phone application, and motivational strategies can increase the level of physical activity in patients with T2DM. Increased physical activity may have positive effects on glycemic control, diabetes-related selfefficacy, and the quality of life.